Ética universal y bioderecho multicultural (2020)
Diversity is part of what we call being human. We need an integrated cross cultural approach to ethics. We should never expect all people to balance the same values in the same way all the time. Nevertheless, there are numerous benefits if the same values, or principles, can be used by ali people and societies. All human beings are found as members of sorne society but ali accommodate sorne individualism within a social niche. All societies have ethical norms and sorne system of ethics. Any international ethical approach to assisting people and systems to making bioethical decisions must consider the biological, social and spiritual origins of humanity. In this fashion, the focus of this article is to address the fundamental question of whether or not a common ethical system could be accepted and applied universally as well as what consequences this could have for biolaw.